Games: Purpose and Potential in Education - Miller, Christopher Thomas; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2009)
The field of Games is rapidly expanding, prompting institutions throughout the world to create game development programs and courses focusing on educational games. As a result, games have also become a hot topic in the area of educational technology research. This increased interest is due to the technological advancement of digital games and the fact that a new, digital generation is emerging with a strong gaming background. Games: Purpose and Potential in Education focuses on the issues of incorporating games into education and instructional design. Ideas of identity development, gender diversity, motivation, and integrating instructional design within game development are addressed since each of these areas is important in the field of instructional design and can have a significant impact on learning. This volume brings together leading experts, researchers, and instructors in the field of gaming and explores current topics in gaming and simulations, available resources, and the future of the field.
Rediscovering the Roots of Games in Education -- What Makes Games Compelling? -- Identity and Gaming -- Fair Game: Designing Games to Bridge the Gender Gap -- Games as a Learning Motivator -- Video Game Pedagogy -- Integrating Instructional Design with Game Development to Optimize Game-Based Learning -- Predicting the Future from Multiple Perspectives: Current Problems and Future Potential for Educational Games.
Keywords: Education; Education -- Data processing; Educational technology; Education; Educational Technology; Computers and Education; Electronic books